2019
DOI: 10.3389/fvets.2019.00190
|View full text |Cite
|
Sign up to set email alerts
|

Framework for Estimating Indirect Costs in Animal Health Using Time Series Analysis

Abstract: Traditionally, cost-benefit analyses (CBAs) focus on the direct costs of animal disease, including animal mortality, morbidity, and associated response costs. However, such approaches often fail to capture the wider, dynamic market impacts that could arise. The duration of these market dislocations could last well after an initial disease outbreak. More generally, current approaches also muddle definitions of indirect costs, confusing debate on the scope of the totalities of disease-induced economic impacts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 57 publications
2
35
0
2
Order By: Relevance
“…A decrease in the producer price during the epidemic and an increase after the disease has been eradicated has been observed previously in simulation-based studies [e.g., (30,32,33)]. However, the present data did not suggest a substantial instantaneous drop in pigmeat price, which has been postulated in cases representing both ASF and other highly contagious animal diseases [e.g., (10,14,19,34)]. This may be because of the EU policies to limit intra-community trade on a regional basis (7).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A decrease in the producer price during the epidemic and an increase after the disease has been eradicated has been observed previously in simulation-based studies [e.g., (30,32,33)]. However, the present data did not suggest a substantial instantaneous drop in pigmeat price, which has been postulated in cases representing both ASF and other highly contagious animal diseases [e.g., (10,14,19,34)]. This may be because of the EU policies to limit intra-community trade on a regional basis (7).…”
Section: Discussionsupporting
confidence: 75%
“…There are also other market considerations which are relevant to the market implications of ASF. For instance, it has been found that the farm gate price of beef in the UK decreased and retail price increased, and the average marketing margin of beef (retail price minus farm gate price) increased by 3.1% following the FMD outbreak when compared with the pre-FMD period (14). The present study did not consider the possibility that ASF would affect consumer preferences.…”
Section: Discussionmentioning
confidence: 61%
“…Specifically, as seen within the past decade in South Korea, a strict approach of stamping out to maintain freedom from FMD without vaccination may not be feasible when the disease pressure is overwhelming [6,[154][155][156][157][158]. Additionally, when indirect costs associated with FMD outbreaks, such as job losses within the livestock sector, and losses associated with reduced tourism are accounted for, the estimated financial benefits of vaccination often increase [159][160][161].…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of farmers that would switch from an alternative vaccine to nVac, as well as the proportion of farmers who would newly start vaccinating against PRRS, significantly depend on these key vaccine characteristics. Therefore, potential socio-economic benefits largely depend on farmers' attitude toward PRRS vaccination and their decisions with respect to switching to a new vaccine (31). The behavior of a few single farmers might have a significant impact at national level, depending on their farm size.…”
Section: Discussionmentioning
confidence: 99%